2016
DOI: 10.1007/s10802-016-0146-8
|View full text |Cite
|
Sign up to set email alerts
|

Impulsivity and Suicidality in Adolescent Inpatients

Abstract: Suicide is the second leading cause of death among adolescents, and impulsivity has emerged as a promising marker of risk. The present study tested whether distinct domains of impulsivity are differentially associated with suicide ideation, plans, and attempts. Adolescents (n = 381; boys = 106, girls = 275) aged 13-19 years (M = 15.62, SD = 1.41) were recruited from an acute, residential treatment program. Within 48 h of admission to the hospital, participants were administered structured clinical interviews a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
68
0
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 119 publications
(79 citation statements)
references
References 63 publications
6
68
0
5
Order By: Relevance
“…Scales loading primarily on this factor were Reflexive Reaction to Feelings (Carver et al ., ), an abbreviated version of the Positive Urgency Measure (Cyders et al ., ), and an abbreviated version of the Negative Urgency scale (Whiteside & Lynam, ). Previous work has replicated the factor structure of scales (Auerbach et al ., ).…”
Section: Methodsmentioning
confidence: 97%
See 2 more Smart Citations
“…Scales loading primarily on this factor were Reflexive Reaction to Feelings (Carver et al ., ), an abbreviated version of the Positive Urgency Measure (Cyders et al ., ), and an abbreviated version of the Negative Urgency scale (Whiteside & Lynam, ). Previous work has replicated the factor structure of scales (Auerbach et al ., ).…”
Section: Methodsmentioning
confidence: 97%
“…Despite overlap in the validity of the emotion‐related impulsivity factors, early studies suggest that it may be important to distinguish between these two factors in understanding psychopathology; that is, there is some evidence that Pervasive Influence of Feelings is more relevant for internalizing conditions such as depressive symptoms, whereas Feelings Trigger Action is more robustly related to externalizing conditions and hypomanic symptoms (Johnson et al ., ). In another study, Pervasive Influence of Feelings was tied to suicidal ideation, whereas Feelings Trigger Action was tied to suicidal actions (Auerbach et al ., ). These findings validate the idea that the two forms of impulsivity differentially guide difficulties with thoughts versus actions in the face of emotion.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…As compared to other dimensions of impulsivity assessed via the UPPS, a recent meta-analysis reported that urgency (particularly negative urgency) showed the strongest correlations with a range of psychiatric symptoms including depression, substance use, anxiety, self-harm/suicidality, and disordered eating [6]. Other studies have documented an even broader profile of symptoms and outcomes that correlate with urgency, including obsessional symptoms of OCD [7, 8], symptoms of Generalized Anxiety Disorder [9], aggression [6, 10], and suicide attempts [11]. Case-control studies also reveal elevations in urgency in a diverse range of diagnostic groups, including individuals diagnosed with bipolar I disorder [12], eating disorders [13], major depressive disorder [14], and schizophrenia [15].…”
Section: Introductionmentioning
confidence: 99%
“…In a meta‐analysis of over 40,000 individuals, emotion‐related impulsivity was compared with other aspects of impulsivity and emerged as the best predictor of every clinical diagnosis and symptom group, including depression, anxiety, eating disorders, borderline personality traits, suicidality, and nonsuicidal self‐injury (Berg et al, ). In clinical populations, emotion‐related impulsivity predicts lower quality of life, higher rates of comorbidity, self‐injury, suicidal action, aggression, and poor social well‐being (Auerbach, Stewart, & Johnson, ; Muhtadie et al, ; Victor, Johnson, & Gotlib, ). Emotion‐related impulsivity appears to be a transdiagnostic vulnerability factor for both internalizing and externalizing disorders (Carver, Johnson, & Timpano, ; Johnson, Carver, & Joormann, ).…”
Section: Introductionmentioning
confidence: 99%